Porter might be right: environmental policy, innovation, and product differentiation - Xie, Wensi (Review of Finance, 2026)
We evaluate the effects of environmental regulation on corporate innovation and real outcomes. Exploiting plant-level regulatory shocks induced by the 1990 Clean Air Act Amendments, we identify firms’ exposure to stricter environmental standards based on whether their plants emit newly regulated pollutants in counties designated as nonattainment. We show that firms more heavily exposed to the regulatory shock increase green innovation, including green process and green product patents, with no corresponding changes in nongreen patenting. The innovation-enhancing effects are concentrated among firms in industries with low external finance dependence and are stronger in areas with more intensive environmental enforcement. In addition, employment declines in response to the regulatory shock, and the effects are more pronounced among firms relying heavily on external finance. Overall, the results support the Porter hypothesis while highlighting the roles of financial capacity and enforcement intensity in shaping firms’ innovation and labor responses to environmental regulation.